Studying the spatial and temporal changes in aeolian sand transport in a wind tunnel using 3D terrestrial laser scanning - Wang, Xuesong; Zhang, Chunlai; Cen, Songbo; Dai, Yujie; Zou, Xueyong (European journal of soil science, 2020)
The spatial and temporal changes in aeolian sand transport are important in modelling wind erosion and parameterizing sand dunes and ripples. In this study, we explored the wind erosion processes that occur in sand beds using a Trimble 3D laser scanner. We found that the erosion intensity varied with distance along the sand bed and that the sand bed surface could be divided into three zones. In the pre‐bowl zone, the sand bed surface showed small and uniform variation, indicating weak erosion intensity in this zone. Downwind of the pre‐bowl zone, the bowl zone developed where the sand surface was eroded seriously and a kind of morphology analogous to blowouts occurred. The post‐bowl zone, which followed the bowl zone, was characterized by alternating accumulation and erosion. Wind velocity affected the spatial development of this bed morphology, whereas the erosion duration only affected the erosion depth. We developed an equation of the form QL = Qsat/(1 + e(−10(L‐s)/k)) to describe the relationship between sediment flux (QL) and bed length (L) in the pre‐bowl and bowl zones and found the fitting coefficients R2 were very high (1.0, 0.98, 0.97 at wind velocities 10.0, 11.0 and 12.0 m s−1, respectively). Using a fine spatial resolution for the measurements revealed features of the sand flux profile that were missed at coarser resolution. However, it will be necessary to use a longer sand bed to study the full length of the post‐bowl zone. Highlights The erosion intensity at different sites of the sand bed was studied. The roughness of the bed surface increased with increasing erosion duration. A sigmoid curve could describe the changes of erosion along the fetch length.